Linkages of Leaves Moisture of Medical Plant (Senecio L.) and Elevation in Shan County - Liao, Bing-Hua (Journal of Drug Delivery and Therapeutics, 2021)
A key plant species (Senecio L.) not only is a vital multilevel functional medicinal material of indications of respiratory tract infections, tonsillitis, pharyngitis, pneumonia, conjunctivitis, enteritis, dysentery, but also it is a widely distributed wide plant species. This plant species is widely distributed elevation from 500m to 1500m in six landscapes in Shan County of China. However, understanding dynamics of leaves moisture of the plants is difficult along elevation. Herein showed that linkages between leaves moisture of the species and elevation is a significant positive connection from 500m to 1000m (P<0.01) as well as linkages between leaves moisture of this species to elevation is a significant negative connection from 1000m to 1500m(P<0.01). Herein provides six types and eco-adaptation for finding new species. Therefore, this study has theoretical and vital practical significance for plants protection along elevation and environmental gradient over the spatial-temporal-environmental-disturbance scales (STEDS) in interdisciplinary research from species diversity, ecosystems diversity and landscape diversity. Keywords: leaves moisture; elevation; relationship; eco-adaptation; eco-functional value; medicinal plant